Supporting multisectoral action: Capacity and nutrition leadership challenges facing Africa - Jerling, Johann; Pelletier, David Louis; Fanzo, Jessica; Covic, Namukolo (International Food Policy Research Institute, 2016)
The aim of this chapter is to present a forward-looking analysis of need for MSN systems and the required three main capacity areas (technical, managerial, and leadership) for effective MSN action to bring about the desired nutrition outcomes for the continent in a sustained manner. The chapter is structured as follows: First we discuss MSN systems, including MSN structures and the system requirements needed to address both nutrition-sensitive and nutrition-specific interventions for wellcoordinated horizontal and vertical action in a multisectoral approach.